Lacunas e perspectivas para o uso sustentável das espécies da sociobiodiversidade brasileira - Silva, Ana Cecília da Cruz (2023)
Brazil is among the five countries considered “megabiodiverse”. From the point of view of flora, a significant part of the species with some non-timber use in the pharmaceutical, food or cosmetics market, or even for local use, is obtained through extractivism, practiced mainly by traditional peoples and communities. For the Brazilian government, the relationship between biodiversity and the diversity of sociocultura systems is defined as sociobiodiversity. In this sense, a list of species of Brazilian sociobiodiversity with food value was instituted, through Interministerial Ordinance n° 163, of May 11, 2016, with the objective of marketing in natura or derived products, within the scope of operations carried out by Minimum Price Guarantee Policy for Sociobiodiversity Products (PGPMBio), through the Food Acquisition Program (PAA) and the National School Feeding Program (PNAE). After two years, this Ordinance was revoked and Interministerial Ordinance n° 284, of May 30, 2018 was instituted and recently Interministerial Ordinance MAPA/MMA n° 10, of July 21, 2021 is in force. The general objective of the present research was to analyze the Interministerial Ordinance MAPA/MMA nº 10/2021 from different perspectives, which permeate a critical look between the revoked Ordinances and the current one, in addition to the scope of the list of sociobiodiversity species, comparing with the identified sociobiodiversity in the state of Sergipe (because it is the smallest state in terms of territory), as well as analyzing the technical-scientific support of the listed species. Thus, in chapter 1 “What does the list of species of Brazilian sociobiodiversity of food value reveal to us?” the objective was to identify changes in relation to the previously published ordinance, as well as to analyze the two lists of sociobiodiversity species based on aspects such as number of species, origin, distribution, risk of extinction and parts of plants used for consumption. Chapter 2 “Fruits of sociobiodiversity: an overview from the state of Sergipe” aimed to carry out a survey of social groups and species of food value and a consultation of the list of Interministerial Ordinance n° 284/2018 to verify which species do not were included in the list or were not cited for Sergipe, as well as which ones did not show reports of use by these groups. Chapter 3 “Conservation of Brazilian socio-biodiversity: a look from the gaps in technical-scientific knowledge” was carried out in order to assess whether official socio-biodiversity species have technicalscientific support. The starting point was the hypothesis: Most of the species of Brazilian sociobiodiversity made official by the Interministerial Ordinance MAPA/MMA nº 10/2021 do not have sufficient technical-scientific support to enable the stimulation of their commercialization on a sustainable basis. For this, seven easily accessible technical-scientific support parameters, considered essential for commercialization on a sustainable basis, were selected. They are: cultivation and domestication; risk of extinction; geographic distribution; information on plant extractivism in the IBGE database; publications on good management practices; deposit of germplasm accessions; and filing of patents. Chapter 4 corresponds to an infographic entitled “Overview of technical-scientific support of sociobiodiversity species for sustainable use”. In the “general final considerations” the research questions were rescued, as well as the discussions around the current scenario. It was found that most species of Ordinance n° 284/2018 are native, but there are seven exotic and five species fit into one of the endangered categories; the registration of 46 native species with food value for social groups in Sergipe that practice extractivism, which are formed by family farmers, residents of agrarian reform settlements, rural communities, extractivists formally recognized as such, fishermen and quilombolas; it is understood that the hypothesis that the majority of species (84,9%) of Brazilian socio-biodiversity made official by the Interministerial Ordinance MAPA/MMA nº 10/2021 does not have satisfactory technical-scientific support to enable the stimulation of their commercialization on a sustainable basis was proven. Suggestions for strengthening the technical-scientific support of sociobiodiversity species were also presented.